The Problems with Neolithization Chronology in The East European Steppe and Forest-Steppe (From the Volga River to the Don River) - Vybornov, A.; Koltsov, P.; Kulkova, M.; Yudin, A.; Goslar, T. (International Journal of Engineering and Technology, 2018)
The article deals with the problems of Neolithic chronology in the steppe and forest-steppe regions from the Volga to the Don. The main criterion of the transition to the Neolithic in the region should be considered the appearance of ceramic ware. In the southern region, the onset of the Neolithic was associated with indigenous processes in the period 7700-7200 years ago, with some influence from the Caucasus. In the northern territories, Neolitization occurred in 7500-7200 years ago and was influenced by the cultures of Central Asia. The early Neolithic on the border between the steppe and forest-steppe in the Volga river basin is represented by the Elshanka complexes with earthenware. The chronological ratio of the Neolithic of the southern and northern territories indicates the influence of steppe cultures on the development of the population in the forest-steppe of the Middle Volga region.
Keywords: steppe and forest-steppe; Neolithic; chronology; radiocarbon analysis; ceramics; interaction of cultures; Kairshak site; Djangar; Varfolomeevka.